Early Adolescent Cyberbullying Victimization, Learning Readiness, and Academic Achievement Among South Australian Students - Williams, Jasmin; Halliday, Sarah (Psychology in the schools, 2025)
ABSTRACT Cyberbullying is an increasingly researched topic in the field of adolescence, largely due to its pervasiveness and negative wellbeing outcomes for victims. However, existing literature in this area largely focuses on those aged above 13 years, despite evidence suggesting that early adolescents (ages 10–13) also experience victimization. Therefore, the aim for this study was to investigate the association between cyberbullying victimization in early adolescence (10–13 years) and learning readiness (perseverance, academic self‐concept, and cognitive engagement) in Grade 6, and academic achievement (numeracy and reading) in Grade 7. This study utilized a population‐based data set of 8,675 South Australian students with 6.5% identifying as cyberbullying victims. Findings revealed that compared to non‐victims, Grade 6 students who experienced cyberbullying had significantly lower learning readiness scores that same year, and poorer numeracy and literacy scores 1 year later, before and after controlling for covariates. Perseverance in Grade 6 was the strongest predictor of Grade 7 numeracy scores, and cyberbullying victimization in Grade 6 was the strongest predictor of Grade 7 reading scores. This study illustrates the negative impact of early adolescent cyberbullying victimization on learning readiness and academic achievement throughout secondary education, highlighting the need for earlier online safety education and greater parental involvement. Summary Cyberbullying victimization in early adolescence (ages 10–13) resulted in significantly poorer learning readiness and academic achievement than non‐victims. Perseverance and cyberbullying victimization in Grade 6 were the strongest predictors of numeracy and reading outcomes in Grade 7 respectively. Despite age restrictions, social media use, and cyberbullying is occurring in early adolescence. This demonstrates the need for earlier online safety education, alongside increased parental guidance, to mitigate the negative effects of cyberbullying and support students' academic development.